Validation of a Fluorescence In Situ Hybridization Method Using Peptide Nucleic Acid Probes for Detection of Helicobacter pylori Clarithromycin Resistance in Gastric Biopsy Specimens - Laura Cerqueira (2013)
Here, we evaluated a previously established peptide nucleic acid-fluorescence in situ hybridization (PNA-FISH) method as a new diagnostic test for Helicobacter pylori clarithromycin resistance detection in paraffin-embedded gastric biopsy specimens. Both a retrospective study and a prospective cohort study were conducted to evaluate the specificity and sensitivity of a PNA-FISH method to determine H. pylori clarithromycin resistance. In the retrospective study (n = 30 patients), full agreement between PNA-FISH and PCR-sequencing was observed. Compared to the reference method (culture followed by Etest), the specificity and sensitivity of PNA-FISH were 90.9% (95% confidence interval [CI], 57.1% to 99.5%) and 84.2% (95% CI, 59.5% to 95.8%), respectively. In the prospective cohort (n = 93 patients), 21 cases were positive by culture. For the patients harboring clarithromycin-resistant H. pylori, the method showed sensitivity of 80.0% (95% CI, 29.9% to 98.9%) and specificity of 93.8% (95% CI, 67.7% to 99.7%). These values likely represent underestimations, as some of the discrepant results corresponded to patients infected by more than one strain. PNA-FISH appears to be a simple, quick, and accurate method for detecting H. pylori clarithromycin resistance in paraffin-embedded biopsy specimens. It is also the only one of the methods assessed here that allows direct and specific visualization of this microorganism within the biopsy specimens, a characteristic that allowed the observation that cells of different H. pylori strains can subsist in very close proximity in the stomach.